Diversity of the Larval Cranial Setae in Palaearctic Notodontidae (Noctuoidea) and and their Taxonomic Distribution - Dolinskaya, I.V. (Вестник зоологии, 2013)
Larval cranial setae of each larval instar of 66 species belonging to 35 genera of Palaeartic Notodontid moths from Ukraine and Far East of Russia (Primorskii krai) was examined with the use of a scanning electron microscope. A comparison with outgroup species — Lasiocampoidea (Lasiocampidae), Sphingoidea (Sphingidae) and Noctuoidea (Erebidae: Lymantriinae, Arctiinae; Noctuidae) is conducted. Main kinds of setae during larval development and their transformation are discussed. Possible apomorphic and plesiomorphic states of the different characters are discussed in relation to the different taxa. С помощью сканирующего электронного микроскопа изучены щетинки головы гусениц всех возрастов 66 видов из 35 родов палеарктических хохлаток из Украины и Приморского края России. Проведено сравнение с представителями внешней группы — Lasiocampoidea (Lasiocampidae), Sphingoidea (Sphingidae) и (Erebidae: Lymantriinae, Arctiinae; Noctuidae). Рассмотрены вероятные направления преобразований в волосяном покрове головы у гусениц различных возрастов. Обсуждаются возможные апоморфные и плезиоморфные состояния признаков различных таксонов.